Factors influencing effective communication and it impact towards Malaysian post pandemic perception: the case of Malaysian government trust / Siti Salbiah Norazan, Suhaimee Sahaar @ Saabar and Wardatul Hayat Adnan - Norazan, Siti Salbiah; Sahaar@ Saabar, Suhaimee; Adnan, Wardatul Hayat (Faculty of Communication & Media Studies, 2024)
A new pandemic with no record of disease has caused a communication crisis in one country. Failure to find appropriate crisis management methods has resulted in a decline in public faith in one government's ability to handle a crisis. Which has contributed to widespread confusion, ignorance, and disinformation. Failure to regulate the phenomenon will result. Thus, the study's main aims are to identify characteristics that influence successful communication during crises, particularly pandemics in Malaysia, and to investigate the effects of good communication on public perception during pandemic crises in Malaysia. The quantitative method will be used to achieve the study's purpose by randomly distributing the survey to 200 Malaysians. Research findings indicate that the Malaysian public's foremost concern was the accessibility of information, scoring at 0.89 with a correlation of 53%. Following closely behind was the credibility of information at 0.76, with a correlation of 42%, trailed by consistency at 0.75 and a 30% correlation, and transparency at 0.67 with a 25% correlation. These factors collectively hold a significant influence, with more than 70% impact on the public's perception of trust in the government. This situation has become critical amidst the endemic due to rampant misinformation. Insufficient public knowledge exacerbates this issue, as highlighted by recent findings. The prevalence of misinformation during the ongoing endemic amplifies the urgency for ensuring accurate and accessible information. Addressing these concerns is pivotal in fostering a more informed society and rebuilding trust between the government and the public during these challenging times.